2023
DOI: 10.1371/journal.pntd.0011550
|View full text |Cite
|
Sign up to set email alerts
|

The public health significance of finding autochthonous melioidosis cases in the continental United States

Alfredo G. Torres

Abstract: Recently, the pathogen that causes melioidosis, Burkholderia pseudomallei, was found in the Gulf Coast region of Mississippi, United States of America, associated with human cases and as bacteria in the soil of affected areas. Therefore, the Centers for Disease Control and Prevention has declared the pathogen as endemic in the continental United States for the first time. This viewpoint discusses some issues that the research, public health communities, and government agencies need to address.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…However, in Limmathurotsakul et al (2016) utilized computer modeling to predict a wider distribution and suggested nearly ubiquitous endemicity throughout the tropical latitudes causing significant morbidity and mortality worldwide ( Limmathurotsakul et al, 2016 ). Consistent with that prediction, B. pseudomallei has been identified in clinical and environmental specimens in areas not previously known to be endemic, including South Asia ( Mukhopadhyay et al, 2018 ; Jayasinghearachchi et al, 2022 ), the Caribbean ( Hall et al, 2019 ; Stone et al, 2020 ), and North America ( Salam et al, 2011 ; Morosini et al, 2013 ; Torres, 2023 ).…”
Section: Introductionsupporting
confidence: 69%
“…However, in Limmathurotsakul et al (2016) utilized computer modeling to predict a wider distribution and suggested nearly ubiquitous endemicity throughout the tropical latitudes causing significant morbidity and mortality worldwide ( Limmathurotsakul et al, 2016 ). Consistent with that prediction, B. pseudomallei has been identified in clinical and environmental specimens in areas not previously known to be endemic, including South Asia ( Mukhopadhyay et al, 2018 ; Jayasinghearachchi et al, 2022 ), the Caribbean ( Hall et al, 2019 ; Stone et al, 2020 ), and North America ( Salam et al, 2011 ; Morosini et al, 2013 ; Torres, 2023 ).…”
Section: Introductionsupporting
confidence: 69%
“…Although most commonly found in tropical and sub-tropical soil in South-East Asia and Australia, climate change is thought to have led to the recent isolation of B. pseudomallei from soil in Mississippi and Texas, and infections were linked to exposure to this soil. (19-21) B. pseudomallei also recently caused a cluster of 4 cases of melioidosis in the U.S. associated with contaminated aromatherapy spray. (22)…”
Section: Introductionmentioning
confidence: 99%